PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KUALITAS LABA DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING - Naula Oktaviani, Rona; Nur, Emrinaldi; Ratnawati, Vince (SOROT, 2015)
ABSTRACT This study aims to demonstrate empirically how the influence of good corporate governance, earnings quality and earnings management, and to investigate whether corporate governance affects the quality of earnings through earnings management as an intervening variable. The data used in this study were obtained financial data from the financial statements of each company and a sample of the book Indonesian Capital Market Directory. The analysis method is path analysis using multiple regression with SPSS version 21. The population used in this study is manufacturing company listed on the Indonesia Stock Exchange in 2009-2012, with a total sample of 64 companies. This research found that the variable institutional ownership, board of directors, and audit committees have a significant effect on earnings management, while managerial ownership and board of directors has no significant effect on earnings management. Good corporate governance variables on earnings quality (institutional ownership, managerial ownership, board of commissioners, board of directors and audit committees) affect the results significantly. Earnings management significantly influence the quality of earnings. The relationship of good corporate governance variables in this case only institutional ownership, board of directors and audit committees have a significant effect on the quality of earnings through earnings management as an intervening variable, while managerial ownership and the board had no significant effect.